PERTUMBUHAN JABON (Anthocephalus cadamba Miq.) PADA LAHAN MARGINAL BERJENIS TANAH ULTISOL DI RIAU - Ahmad Junaedi (Jurnal Pemuliaan Tanaman Hutan, 2018)
Study on growth of jabon (Anthocephalus cadamba Miq) as native tree species that suitable for pulpwood on ultisol-soil land is required, as most pulpwood plantation occur in this type of soil. The experiment was conducted in ex Acacia mangium (second rotation) in Riau to evaluate the growth performance of jabon on marginal land ultisol soil. This study assigned experiment plots of jabon with three planting spaces (2 m × 2 m; 2 m × 3 m and 3 m × 3 m) and four blocks in Randomized Block Design. The poor growth was exhibited by jabon on marginal land ultisol. It was suggested that the poor growth related to the negative effects of low N and P soil, high Al soil, and threats of pest, disease, weed as well. The result study indicated that jabon was not suitable to be developed as pulpwood species in marginal lands ultisol of pulpwood plantation in Riau.